The Effects of Co-Enzyme Q10 and Caffeine on Morphometric Characteristics of Queen Honey Bees - Samet Okuyan; Paul Cross (Turkish Journal of Agriculture: Food Science and Technology)
Honey bee queen quality is a critical factor of colony performance. Indications of such qualities can manifest themselves through morphological traits such as wet weight and thorax width. Improving such characteristics is driven in part by nutritional provision in queen-cell-builder hives. We investigated the potential to improve queen quality by adding coenzyme Q10 (endogenous antioxidant) and caffeine (central nervous system stimulator) to feeder syrup in queen-cell-builder colonies for 15 and 20 days prior to grafting, two sets of queens were reared. We recorded subsequent wet weight, body length, head width and length, thorax and wing width and length, and spermathecae diameter. The queen-cell acceptance rate was not affected by either treatment or graft period. Coenzyme Q10 increased wet weight, body and wing length in the first graft, and thorax width, wing length and spermathecae diameter in the second graft. The caffeine treatment increased head and thorax length in first graft and thorax width in the second. A mix of the two substances (coenzyme Q10 and caffeine) increased head width in the first graft and spermathecae diameter in the second graft. This study suggests that the application of coenzyme Q10 to cell-builder colonies at least 15 days prior to grafting can increase reared wet weight (the most significant quality indicator) and thorax width of queen bees.